2010
DOI: 10.1111/j.1574-6976.2010.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression during swarmer cell differentiation inProteus mirabilis

Abstract: The gram-negative bacterium Proteus mirabilis can exist in either of two cell types, a vegetative cell characterized as a short rod and a highly elongated and hyperflagellated swarmer cell. This differentiation is triggered by growth on solid surfaces and multiple inputs are sensed by the cell to initiate the differentiation process. These include the inhibition of flagellar rotation, the accumulation of extracellular putrescine and O-antigen interactions with a surface. A key event in the differentiation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 79 publications
1
77
0
Order By: Relevance
“…It results in the formation of characteristic rings of bacterial growth on the agar plate ( fig. 1) (VERSTRAETEN et al 2008, MORGENSTEIN et al 2010, RÓŻALSKI & STĄCZEK 2010.…”
Section: Swarming Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…It results in the formation of characteristic rings of bacterial growth on the agar plate ( fig. 1) (VERSTRAETEN et al 2008, MORGENSTEIN et al 2010, RÓŻALSKI & STĄCZEK 2010.…”
Section: Swarming Phenomenonmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a surface component of these bacteria, seems to be important in the swarming phenomenon, however, its exact role has not been described. Mutation in the wzz region encoding O-antigen chain, as well as in genes waaD and waaC required for the core region of LPS are impaired in swarming growth (MORGENSTEIN et al 2010). Swarmer cells translocation is facilitated by an extracellular acidic polysaccharide designated as Cmf (colony migration factor), which acts as a lubricant, reducing surface friction (GYGI et al 1995).…”
Section: Swarming Phenomenonmentioning
confidence: 99%
“…It showed that sub-inhibitory concentrations of diclofenac inhibited the swarming and swimming motilities significantly which may affect the infection spread which may influence the pathogenesis as a consequence. Several factors participated in the regulation of swarming motility including the up-regulator of flagellar master operon (Umo) proteins and other factors reviewed elsewhere (Morgenstein et al, 2010). Moreover, all flagellum-related genes are arranged within a single 53.3-kb locus (Pearson et al, 2008), which may indicate the significance of inhibition of the transcriptional regulator on motility.…”
Section: Discussionmentioning
confidence: 99%
“…Proteus is a causative agent of wide range of infections; the potential of its virulence is not only due to production of several extracellular enzymes, but also due to inherent capability of pretrichrous flagellar translocation and its biofilm formation capability (Morgenstein et al, 2010;Armbruster and Mobley, 2012). In the last decades, resistance development is one of the serious emerging problems and it is owed to genotypic and/or phenotypic modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation